2013
DOI: 10.1371/journal.pone.0055004
|View full text |Cite
|
Sign up to set email alerts
|

Brain Region Specific Pre-Synaptic and Post-Synaptic Degeneration Are Early Components of Neuropathology in Prion Disease

Abstract: Synaptic abnormalities, one of the key features of prion disease pathogenesis, gives rise to functional deficits and contributes to the devastating clinical outcome. The synaptic compartment is the first to succumb in several neurodegenerative diseases linked with protein misfolding but the mechanisms underpinning this are poorly defined. In our current study we document that a focal intrahippocampal injection of the mouse-adapted 22L scrapie strain produces a complex, region-specific pathology in the brain. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
19
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 33 publications
0
19
0
Order By: Relevance
“…As previous terminal stages studies would have predicted, there is some cerebellar tropism in the 22L strain that is not obvious in ME7 and 79A strains, and indeed 22L shows somewhat weaker synaptic loss, microglial activation and PrP Sc deposition in the CA1 of the hippocampus with respect to the dentate gyrus/CA3 region. However, that 22L can produce CA1 synaptic loss is significant, and this has now been confirmed by electron microscopy studies [22]. On the whole 79A produces rather similar early pathology to ME7.…”
Section: Discussionmentioning
confidence: 79%
“…As previous terminal stages studies would have predicted, there is some cerebellar tropism in the 22L strain that is not obvious in ME7 and 79A strains, and indeed 22L shows somewhat weaker synaptic loss, microglial activation and PrP Sc deposition in the CA1 of the hippocampus with respect to the dentate gyrus/CA3 region. However, that 22L can produce CA1 synaptic loss is significant, and this has now been confirmed by electron microscopy studies [22]. On the whole 79A produces rather similar early pathology to ME7.…”
Section: Discussionmentioning
confidence: 79%
“…In contrast to early synaptic changes in the stratum radiatum of the hippocampus, which are virtually identical to those detected with a different prion strain (ME7), 3 dendritic rather than synaptic disintegration was observed in the cerebellum, even in late-stage disease. Similar levels of protease-resistant pathological prion protein have been found in the hippocampus and in the cerebellum of ME7 and 22L prion strains 2 , 4 . In Creutzfeldt-Jakob disease, the most common prion disease in humans, cerebellar alterations are well documented; 5 notably, flattening and reduction of dendritic arbors of Purkinje cells have been reported 6 .…”
mentioning
confidence: 59%
“…Degenerative changes associated with the Purkinje cells were dominated by dendritic malformations, while the major synaptic inputs to the cerebellum were preserved. Electron microscopy confirmed that the spiny branchlets on Purkinje neurons and the parallel and climbing fiber terminals were both intact, whereas the Purkinje dendrites degenerated progressively 2 . We concluded that neuronal vulnerability to pathological protein misfolding is strongly dependent on the structure and function of the target neurons.…”
mentioning
confidence: 71%
See 2 more Smart Citations